THU0367 Familial Mediterranean Fever (FMF): A Single Center Clinical-Genetic Study. (10th June 2014) - Repa, A.; Bertsias, G.; Fragouli, E.; Fanouriakis, A.; Kabouraki, E.; Goulielmos, G.; Boumpas, D.; Sidiropoulos, P.
Abstract : Background: FMF is the prototype of autoinflammatory disorder characterized by recurrent self-limited inflammatory episodes. 1 FMF is an autosomal recessive disease that is prevalent among eastern Mediterranean populations. The responsible gene ( MEFV ) encodes for the pyrin protein (or marenostrin) 2, 3 and the most serious complication of the disease is amyloidosis Objectives: To report on the clinical manifestations and genotypic variation in a cohort of FMF patients followed at the University Hospital of Crete. Methods: During the period 2005-2013, 160 patients were evaluated for possible FMF. The diagnosis was established according to clinical judgment and genetic analysis for the 12 most frequent MEFV mutations (based on the "FMF Strip Assay"). We reviewed the clinical, laboratory and genetic characteristics in patients who are evaluated in the clinic on a regular basis. Results: 106 patients (50% women) were diagnosed with FMF with an average age 23.5 years (range 1-60) at the time of first attack. Combined MEFV heterozygosity and homozygosity was found in 31.1% of the patients, while 19.9% of patients carried no mutation. MEFV M694V was the most frequent (49.5%) mutation. The most frequent presenting manifestations were abdominal pain and fever (Table 1 ). 78% of patients are receiving colchicine 1 mg/day, while 13% require >1 mg/day to prevent attacks. Only one patient receives IL1-blockade (anakinra) due to colchicine failure. No patients discontinued colchicine due to side effect. Amyloidosis developed in 2 patients. There were no differences in clinical manifestation or response to treatment among patients with a single mutation, two mutations, or no MEFV mutation at the time of diagnosis. Conclusions: In a cohort of FMF patients in the Mediterranean island of Crete, the most common MEFV mutation was M694V and all but two patients had excellent prognosis on colchicine therapy. Genotype did not correlate with clinical manifestations or response to treatment. References: Sohar E, Gafni J, Pras M, Heller H (1967) Familial Mediterranean fever. A survey of 470 cases and review of the literature.Am J Med 43:227–2532 French FMF Consortium. A candidate gene for familial Mediterranean fever. Nat Genet. 997;17:25-31. International FMF Consortium. Ancient missense mutations in a new member of the RoRet gene family are likely to cause familial Mediterranean fever. Cell. 1997;90:797-807. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3363